2018
DOI: 10.1186/s12864-018-4845-0
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular stoichiogenomics reveal cell evolution and electrostatic interaction mechanisms in cytoskeleton

Abstract: BackgroundEukaryotic cells contain a huge variety of internally specialized subcellular compartments. Stoichiogenomics aims to reveal patterns of elements usage in biological macromolecules. However, the stoichiogenomic characteristics and how they adapt to various subcellular microenvironments are still unknown.ResultsHere we first updated the definition of stoichiogenomics. Then we applied it to subcellular research, and detected distinctive nitrogen content of nuclear and hydrogen, sulfur content of extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…Membrane and extracellular proteins in yeast are relatively reduced and oxidized, respectively 29. Similarly, a relatively high carbon oxidation state of extracellular proteins is implied by a decreased hydrogen content, which was documented in a stoichiogenomic analysis of the proteomes of 12 eukaryotic organisms 51. Furthermore, secreted proteins that are upregulated in hypoxia are more oxidized than proteins in cell extracts that are upregulated in hypoxia (Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…Membrane and extracellular proteins in yeast are relatively reduced and oxidized, respectively 29. Similarly, a relatively high carbon oxidation state of extracellular proteins is implied by a decreased hydrogen content, which was documented in a stoichiogenomic analysis of the proteomes of 12 eukaryotic organisms 51. Furthermore, secreted proteins that are upregulated in hypoxia are more oxidized than proteins in cell extracts that are upregulated in hypoxia (Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, we found that, except some oncogenes, the up-regulated proteins with high oxygen contents were involved in cell division, including cytoskeleton, cytoskeleton associated proteins, cyclins and signaling proteins in cell cycle progression. Studies have shown that the cytoskeleton proteins are rich of acid amino acids and oxygen 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Unregulated cell cycle leads malignant proliferation, which is the most typical feature of cancer [60], and error-prone phenotypes in DNA replication often lead to serious, unexpected spread of cancer. Our previous studies have shown that cytoskeleton proteins possess much acidic amino acids and high oxygen contents [26]. Rapid proliferation and division of tumor cells require frequent dissociation and recombination of cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…By assessment of differential usage of key elements (e.g., nitrogen, N) in proteins, it provides an entire new perspective for investigating interactions of proteins evolution and environment [25]. Nutrient limitation theory suggests that natural selection caused by limited element supplies might bias to monomer usage to reduce the corresponding element costs, because amino acids and nucleotides are different in element counts [26]. This has been evidenced in plants and microbes.…”
Section: Introductionmentioning
confidence: 99%